International Literature Review on Congestion Mitigation Methods - Córdova Vidal, Rai Edú (2022)
Every person who travels by car, especially those who live in or nearby dense urban areas, is well familiarized with traffic jams on the highway. With the aim of mitigating traffic congestion, several technologies have been developed over the years to design intelligent transportation systems capable of controlling traffic dynamically or statically. In other words, they are either programmed to adapt to current traffic conditions or have preset working modes saved in their system. Other solutions to the congestion problem include the opening of part-time shoulders, high-occupancy vehicle lanes, congestion pricing, coordination between adjacent ju-risdictions, transportation agencies temporarily taking control of traffic during heavy weather or at accident scenes, among others. Their implementation has resulted to be beneficial for the overall traffic flow by providing reliable travel times as well as by lowering environmental degradation, improving the quality of life of drivers and giving highway users, freight companies and even governments opportunities to save money and reduce unnecessary money expenses.